Thermoelectric properties of Fe1.5TiSb1−xSnx and Fe1.5Ti1−xYxSb Heusler alloys. (2021) - Kalugina, Anna; Taranova, Anastasiia; Novitskii, Andrey; Karpenkov, Dmitriy; Sedegov, Alexey; Kurichenko, Vladislav; Voronin, Andrey; Miki, Hiroyuki; Patnaik, Satyabrata; Khovaylo, Vladimir
Abstract: The effects of Sn and Y doping on thermoelectric properties of a Heusler Fe1.5 TiSb semiconductor was studied. Samples of Fe1.5 TiSb1− x Sn x and Fe1.5 Ti1− x Y x Sb solid solutions ( x  = 0; 0.05; 0.1) were synthesized by arc and induction melting, annealed at 1073 K, and examined by X-ray diffraction and scanning electron microscopy with energy-dispersive X-ray analysis. All alloys of the solid solutions crystallize in the half Heusler structure (space group F4̅3m), and have dominant phase Fe1.33 TiSb with a small amount of precipitates. Measurements of the transport properties revealed that all the alloys are p -type semiconductors. In the parent Fe1.5 TiSb, substitution of Sb by Sn results in increasing electrical conductivity σ, whereas substitution of Ti Y decreases σ . Measurements of thermal conductivity κ showed that it decreases with substitution Sb for Sn, as well as with substitution of Ti for Y. The highest zT  = 0.14 (at 473 K), was found for the composition Fe1.5 TiSb.